2012
DOI: 10.1037/a0026978
|View full text |Cite
|
Sign up to set email alerts
|

Potential causal relationship between depressive symptoms and academic achievement in the Hawaiian high schools health survey using contemporary longitudinal latent variable change models.

Abstract: There is a relatively consistent negative relationship between adolescent depressive symptoms and educational achievement (e.g., grade-point average [GPA]). However, we are less certain of the causal direction for this association due to the lack of longitudinal data with both indicators measured across at least two time periods, and due to the lack of application of more sophisticated contemporary statistical techniques. We present multivariate results from a large longitudinal cohort-sequential study of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 93 publications
(193 reference statements)
4
53
0
2
Order By: Relevance
“…On the other hand, psychological distress among nursing students can result in the possession of many negative personal thoughts and emotions that may affect their communication abilities. Hishinuma et al (2012) indicated that poor psychological wellbeing was related inversely to ineffective communication among nursing students. get to the point quickly and keep things moving.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, psychological distress among nursing students can result in the possession of many negative personal thoughts and emotions that may affect their communication abilities. Hishinuma et al (2012) indicated that poor psychological wellbeing was related inversely to ineffective communication among nursing students. get to the point quickly and keep things moving.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that depressive symptoms affected subsequent academic achievement with the possibility of a mediating third variable (Hishinuma, Chang, McArdle, & Hamagami, 2012). Another group of researchers showed that children with anxiety disorders reported more somatic complaints than did the non-anxious children, and the higher frequency of somatic complaints specifically predicted poorer academic performance (Hughes, Lourea-Waddell, & Kendall, 2008).…”
Section: Prediction Effects Of Problem Behaviors On Academic Achievementmentioning
confidence: 99%
“…These elements include personal growth, self-acceptance, purpose of living, autonomous behaviour, positive relationship with people, and mastery of environment (Shojaee & French, 2014). Hishinuma et al (2012) has argued that poor psychological wellbeing is related inversely to ineffective communication. Literatures have shown that good communication could increase satisfaction and trust.…”
Section: Introductionmentioning
confidence: 99%